2023
DOI: 10.1007/s00405-022-07795-9
|View full text |Cite
|
Sign up to set email alerts
|

Hearing rehabilitation and microbial shift after middle ear surgery with Vibrant Soundbridge in patients with chronic otitis media

Abstract: Introduction Patients with otitis media (OM) encounter significant functional hearing impairment with conductive, or a combined hearing loss and long-term sequelae involving impaired speech/language development in children, reduced academic achievement and irreversible disorders of middle and inner ear requiring a long time therapy and/or multiple surgeries. In its persistent chronic form, Otitis media (COM) can often only be treated by undergoing ear surgery for hearing restoration. The persiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…Full text review of these 290 articles was conducted, and a total of 52 articles were selected for inclusion (Fig. 1) (13–64). Critical appraisal of studies indicated an acceptably low risk of bias for the majority of included studies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Full text review of these 290 articles was conducted, and a total of 52 articles were selected for inclusion (Fig. 1) (13–64). Critical appraisal of studies indicated an acceptably low risk of bias for the majority of included studies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Without sufficient therapy, there is no way out of this descending spiral. This is especially the case in therapy-persistent COM due to antimicrobial resistance; up-to-date, middle ear surgery, with the complete removal of the inflammation foci and appropriate surgical rehabilitation, including the reconstruction of the tympanic membrane, the classic hearing structures or implantable hearing devices, such as an active middle ear implant (VSB), is the only way to treat this disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…COM is connected with different inflammatory processes within the middle ear [ 9 , 10 ], whereas infections with Gram-negative bacteria, such as Pseudomonas aeruginosa , are the main cause of COM development [ 8 , 11 ]. In this context, lipopolysaccharide (LPS) is a major component of the cellular envelope of Gram-negative bacteria and it has been shown in mice that LPS-induced COM leads to different inflammatory reactions, such as the infiltration of macrophages and expression of inflammatory cytokines [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic otitis media (COM) is a chronic inflammation of the middle ear and in most cases is associated with different bacterial infections of the mastoid cavity. COM is the most widespread clinical pathology that is associated with ear discharge and hearing loss 1 , 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Without sufficient therapy, there is no way out of this descending spiral. Especially, in antimicrobial-persistent COM, middle ear surgery with complete removal of the inflammation foci and appropriate surgical rehabilitation, including reconstruction of the tympanic membrane, the middle ear ossicles or implantable hearing devices, is the only way to treat this disease 2 .…”
Section: Introductionmentioning
confidence: 99%